PENGARUH PEMANFAATAN MEDIA AUDIO VISUAL TERHADAP HASIL BELAJAR SISWA PADA MATA PELAJARAN PENDIDIKAN AGAMA ISLAM DI SMP ISLAM AL-MA’ARIF 01 SINGOSARI - Fitria Ainun Naim; Muhammad Hanief; Mohammad Afifulloh (Vicratina : Jurnal Ilmiah Keagamaan, 2019)
This study aims to determine the differences in learning outcomes between students who are taught using audio-visual media with student learning outcomes without audio-visual media on Islamic Education subjects. The research design used was an experimental research design (quasy experimental design). The population of this study was the eighth grade students of Al-Ma'arif 01 Islamic Middle School Singosari. Samples are class VIII B and VIII E which are determined by purposive sampling. Student learning outcomes data obtained through questionnaire observation and tests (pre-test, post-test). Analysis of data on the use of audio-visual media on student learning outcomes was carried out using t-test analysis (paired sample t test) with the help of SPSS 16 for windows. Based on the results of calculations, it shows that there are differences in learning outcomes of students who are taught using audio-visual media with learning outcomes without audio-visual media in Islamic Education. Students learned using audio-visual media get an average of the learning outcomes obtained from the post-test at 90.60 while students who study without using audio visual media get an average learning outcome of 71.53. Calculations in the control and experimental class get t count of 11,262 > t table 2.042 with a significance level of 5% which means that Hi is accepted and rejects Ho so that there is significant influence on the application of audio-visual media to student learning outcomes in Islamic Education subjects in Islamic Middle School Al-Ma'arif 01 Singosari. Keywords: audio visual, learning outcomes, Islamic education